Medial vs lateral unicompartmental knee arthrroplasty: clinical results - Fiocchi, Andrea; Condello, Vincenzo; Madonna, Vincenzo; Bonomo, M.; Zorzi, Claudio (Acta Biomedica Atenei Parmensis, 2017)
Unicompartmental Knee Arthroplasty (UKA) is a common procedure for the management of isolated osteoarthritis. UKA is considered less invasive compared to total knee arthroplasty, associated with less operative time, blood loss and faster recovery. Isolated lateral osteoarthritis is a relatively uncommon clinical problem, with an incidence about ten times lower than the medial compartment. In fact, lateral UKA are about 5-10% of the total amount of the UKAs. In addition, it’s historically considered more challenging and with poorer results. The aim of this paper was to compare current indications, modes of failure, survivorship and clinical results of medial and lateral UKA by a narrative review of the latest literature.